Considerations in the design of a low‐voltage power MOSFET technology. Issue 15 (22nd October 2019) - Rutter, Phil
Abstract : Discrete low‐voltage power metal‐oxide‐semiconductor field effect transistors are used in a wide variety of applications with each application relying on different aspects of device behaviour. The conflicting requirements of these applications along with constraints such as legislation, industrial base, and intellectual property have resulted in a diverse array of technologies available in the market. This study outlines the many considerations that are faced when designing a high‐performance silicon power MOSFET technology contrasting the trade‐offs involved as factors such as on‐state resistance, switching performance, reliability, and robustness in the application are optimised.